Answer:
See explanation below.
Explanation:
We need to prove that there are no solutions of the equation: x =
![√(-5x-6)](https://img.qammunity.org/2020/formulas/mathematics/high-school/a39p9yffnjgph6favzj797306tz2nvkj1o.png)
Let's start trying to solve this equation:
![x = √(-5x+6) \\x^(2) =-5x + 6\\x^(2) +5x - 6 = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/qq323y9uhg769u49u6vcovu4ksx323n79j.png)
To solve this equation, by factorizing the equation we get:
![x^(2) +5x-6 = 0\\(x +6)(x-1) = 0\\x=-6\\x=1](https://img.qammunity.org/2020/formulas/mathematics/high-school/f07xicz695tcz1zavh0tsyoxonurxmzxcw.png)
- Now we're going to substitute these numbers in the original equation:
For x = -6 we have:
x =
![x=√(5x-6) \\6=√(5(-6)-6) \\6=√(-30-6) \\6= √(-36)](https://img.qammunity.org/2020/formulas/mathematics/high-school/5o4c3mnf2jen70nxn8cj6w4u1v81q24xjj.png)
But √-36 has no solution in the real numbers and therefore it cannot equal 6.
![x = √(-5x-6) \\1=√(-5(1)-6)\\1=√(-5-6) \\1=√(-11) \\1\\eq √(-11)](https://img.qammunity.org/2020/formulas/mathematics/high-school/mgrf9lgsna73ypp7xgqx7z78b8o6cx9xtp.png)
Since the left side is different than the right one, this is not a solution.
Therefore the equation has no solution in the real numbers